2019
DOI: 10.3390/nu11102326
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Evaluating the Effects of a Nutritional Supplement Intervention on Cognition, Mood States, and Mental Performance in Video Gamers

Abstract: Cognitive function is critical for successful prolonged performance in eSports. This double-blind placebo-controlled study examined the effect of an inositol-enhanced arginine silicate oral supplement on cognitive performance and energy in eSports athletes. Sixty healthy men and women who spent 5 or more hours a week playing video games were randomly assigned to take supplement or placebo for 7 days. On day 1 and 7, before and 15 min after dosing, subjects completed the Trail Making Test (TMT), Parts A and B; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
2
19
0
2
Order By: Relevance
“…The results demonstrated that attention and cognitive flexibility assessed by TMT-B was improved in the 6gIG, whereas no significant changes were observed in either the 3gIG or PCG. An effect of intervention on TMT-B was observed, and the 15-s improvement of 6gIG was similar to the intervention effects reported by previous intervention studies ( 32 , 33 ). The faster performance of the TMT-B suggests the improvement of the ability to concentrate on the task, pay attention to multiple tasks and memorize information needed for doing tasks, which is related with working memory.…”
Section: Discussionsupporting
confidence: 87%
“…The results demonstrated that attention and cognitive flexibility assessed by TMT-B was improved in the 6gIG, whereas no significant changes were observed in either the 3gIG or PCG. An effect of intervention on TMT-B was observed, and the 15-s improvement of 6gIG was similar to the intervention effects reported by previous intervention studies ( 32 , 33 ). The faster performance of the TMT-B suggests the improvement of the ability to concentrate on the task, pay attention to multiple tasks and memorize information needed for doing tasks, which is related with working memory.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Tartar et al [12] reported that 1-day and 7-days of 1600 mg of inositolenhanced bonded arginine silicate supplementation increased perceptions of energy and decreased TMT-B test errors compared to placebo. Additionally, fatigue, TMT-B time, and TMT-A score significantly improved from baseline while post-game TMT-A time improved with ASI + I supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…This study examined whether inositol stabilized arginine silicate, a substance shown to increase arginine and NO levels, and whether additional inositol affects cognitive function, reaction time, and/or memory in experienced e-sport gamers following a 1-h gaming challenge. Given evidence in prior studies [4,11,12], we hypothesized that ingestion of ASI + I prior to a gaming challenge would affect cognitive function. Results of this study provide evidence that acute ASI + I ingestion improved primary outcomes of reaction time and working memory among e-sport gamers in several cognitive function related tests with no reported stimulant-related side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations